2001
DOI: 10.1037/1076-8998.6.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Unintended consequences: Organizational practices and their impact on workplace safety and productivity.

Abstract: Managers often implement new organizational practices to improve firm performance while neglecting possible side effects. This study examines the relationship between 6 organizational practices and both productivity and injury rates in 86 small manufacturing firms. The use of performance-based pay was associated with higher injury rates and lower productivity (on 1 of 2 measures). The opposite pattern held for training: Training hours were negatively related to the injury rate and positively related to 1 measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 40 publications
(43 reference statements)
4
83
0
1
Order By: Relevance
“…Many of these efforts have been directed towards the four levels of hazard control: hazard removal, engineering controls, administrative controls, and personal protective equipment (Kaminski, 2001). Even though some researchers have suggested that 90% of accidents can be attributed to human error (McKenna, 1983), the study of the relationship between individual differences and accidents and injuries has received less attention.…”
Section: Individual Differences and Accidentsmentioning
confidence: 99%
“…Many of these efforts have been directed towards the four levels of hazard control: hazard removal, engineering controls, administrative controls, and personal protective equipment (Kaminski, 2001). Even though some researchers have suggested that 90% of accidents can be attributed to human error (McKenna, 1983), the study of the relationship between individual differences and accidents and injuries has received less attention.…”
Section: Individual Differences and Accidentsmentioning
confidence: 99%
“…Coates and Sara A. Quandt appeared in two articles in the bibliographic portfolio and were the most commonly cited in the references with five citations each. The second most prominent article in the portfolio was "Unintended consequences: organizational practices and their impact on workplace safety and productivity" [13], which had been quoted five times in references with 112 citations on Google Scholar. These articles are available, respectively, in the Journal of Construction Engineering and Management and Journal of Occupational Health Psychology.…”
Section: Resultsmentioning
confidence: 99%
“…Poultry industry companies provide, to workers, limited training on security purposes and the effects of the pace of work on them, so that many do not understand how their activities in the production line are related to the musculoskeletal injuries they acquire [10,11]. Mohamed [12], mentions the importance of more focus on management measures that can align the strategic focus on security for the entire organization, and Kaminski [13] points out that the significant negative relationship between capital intensity and injury rates suggests a relationship between risk controls and injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Small firms are thus better able to cater to customers' needs, to respond to changing consumer tastes and to satisfy specific market niches (Piore and Sabel, 1984;Salais and Storper, 1992). Such firms also have a "thinner" organization, which facilitates a lower span of control and ensures a quicker response time and decision-making process (Jensen and Meckling, 1976;Knight and Cavusgil, 1996). In this regard, Bonaccorsi (1992) and Jolly et al (1992) specifically report evidence of the earlier and quicker internationalization of small, technology-intensive firms.…”
Section: Empirical Designmentioning
confidence: 99%